Epistemology As A Way Of Knowing - Daruhadi, Gagah (Syntax Corporation Indonesia, 2024)
Epistemology as a branch of philosophy determines the character of knowledge, and even determines which truths are considered worthy of acceptance, and which ones are worthy of rejection. Therefore, there are a number of questions that are usually asked to examine issues in epistemology, namely what is knowledge, what is the source and basis of knowledge? Is this knowledge definitive truth or just conjecture? In an era of globalization and rapid information development, understanding the nature of knowledge and how we obtain it is becoming increasingly important. Epistemology, which is the study of knowledge, has undergone significant transformation in recent decades. This paper explores the evolution of epistemological thought, focusing on contemporary approaches such as feminist epistemology, social, postmodernism, and global perspectives on knowledge. The qualitative research method used in writing this article is literature study. By comparing old views with new ones, this paper describes how these new views